Optimalisasi Link and Match SMK Dengan Mitra Dudi Melalui Pengembangan Aplikasi SMK Integration System (E-Sis) - Rustanto, Agung Edi; Khasanah, Khasanah; Waluyo, Surryanto Djoko (Universitas Muhammadiyah Mataram, 2026)
Abstract: The objective of this Community Service Program (PkM) is to enhance students’ career planning at SMK Mathla'ul Anwar and integrate it with the needs of industry partners (DUDI) through the development of the SMK Integration System (e-SIS) application. The implementation methods include needs analysis, socialization, training, technology application, and mentoring. The stages of the program consist of situation and partner condition analysis, preparation and development of appropriate technology, socialization and training, technology implementation and mentoring, as well as program evaluation and sustainability. The implementation of this program resulted in several achievements: overall, the program was successfully implemented, and its outcomes were achieved as planned. (1) The development of the SMK Integration System (e-SIS) application has successfully accommodated all the data required by the school to improve students’ career planning in a more systematic and comprehensive manner. (2) The SMK Integration System (e-SIS) application has been developed to integrate data needed by teachers, students, parents, and industry partners (DUDI). (3) The SMK Integration System (e-SIS) application has been implemented and is operating effectively at SMK Mathla’ul Anwar Pakisjaya. (4) The successful implementation of the SMK Integration System (e-SIS) has contributed to enhancing students’ career planning at SMK Mathla’ul Anwar Pakisjaya.Abstrak: Tujuan pelaksanaan pengabdian kepada Masyarakat ini adalah Tujuan pelaksanaan PkM ini yaitu meningkatkan perencanaan karir siswa di SMK Mathla'ul Anwar dan mengintegrasikannya dengan kebutuhan pada mitra DUDI melalui pengembangan aplikasi SMK Integration System (e-SIS). Metode Pelaksanaan kegiatan yaitu melalui analisis kebutuhan, sosialisasi, pelatihan, penerapan teknologi dan pendampingan. Tahapan pelaksanaan kegiatan yaitu (1) Tahap Analisis Situasi dan Kondisi Mitra, (2) Tahap persiapan dan pengembangan teknologi tepat guna (TTG), (3) Tahap Sosialisasi dan Pelatihan, (4) Tahap Penerapan teknologi, dan Pendampingan (5) Tahap evaluasi dan Keberlanjutan program. Berdasarkan dari implementasi kegiatan ini diperoleh hasil yaitu secara keseluruhan berjalan dengan baik dan capaiannya sesuai dengan yang telah direncanakan. (1) Hasil pengembangan Aplikasi SMK Integration System (e-SIS) yaitu telah berhasil mengakomodasi semua data yang diperlukan oleh sekolah dalam rangka meningkatkan perencanaan karir siswa secara lebih sistematis dan komprehensif. (2) Aplikasi SMK Integration System (e-SIS) telah dikembangkan dan mampu mengintegtasikan data yang diperlukan oleh guru, siswa, orang tua dan mitra DUDI, (3) Aplikasi SMK Integration System (e-SIS)telah diterapkan dan berjalan dengan baik di SMK Mathla’ul Anwar Pakisjaya, (4) Keberhasilan penerapan Aplikasi SMK Integration System (e-SIS) dapat meningkatkan perencanaan karir siswa di SMK Mathla’ul Anwar Pakisjaya.